Occurrence of tremolitic asbestos in Nowshera Formation Ghundai Tarako, district Swabi, north Pakistan - Jehan, Noor; Ahmad, Irshad (Journal of Himalayan Earth Sciences, 2007)
The Ghundai Tarako area is located about 11 kilometers to the northwest of Swabi town. The area consists of dolomitic and calcitic marbles of the Nowshera Formation intruded by mafic dykes and sills. Asbestos occurs along a contact between the mafic sill and marble. X-Ray diffraction analysis shows that the type of asbestos is fibrous tremolite belonging to the amphibole group. Extensive mining of marble is in progress in the area under consideration. As a result, airborne tremolitic asbestos is released in the air and might become the potential source of adverse environmental impacts. Skin allergies and asthma are commonly observed diseases among the marble miners in the area.